INITIAL ESTIMATION ON THE CAUSE OF SPILLED OIL IN THE VIETNAMESE COASTAL ZONE IN THE FIRST HALF OF 2007 YEAR - Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2008)
From January to May 2007, the floating oil attached the coastal areas and some islands of 20 coastal  provinces in large scale, from Ha Tinh to the south. The consequences of this event are heavy for forthcoming and long time, meanwhile the cause of spilled oil has been not determined. The existing suppositions can be included into two main groups: Firstly, the causes have been from offshore production  sites working or stopping inside or outside of Vietnamese Sea, secondly, the causes are from oil transportation or other navigation activities which purposefully or inpurposefully have dumped oil on their routes, or shipping accidents on the sea. Beside. there are some different opinions, but little persuasion. Based on the analysis of existing information and data, the author of this paper indicates that the cause of the  event has been not from any concrete perpetrator at any concrete moment, but from the annually accumulative consequences of wasted oil into the sea from many different sources. From them, the oil  wasres and ballast from shipping on the international navigation routes or in harbor waters have been the sources of most importance. The wasted oil of multi-sources has been being accumulated into the slicks  concentrating in the determined offshore waters, and floating on the sea after rit e relatively stable currents by seasons. The phenomena of El-Nino lasting from September of last year to present has made the climatic  turbulence and changed in hydrological structure of sea. So that, the offshore waters bearing oil slicks has run to coasts and floated oil has been appeared in the large scale.